Standard specification for Seamless and Electric-Welded Low-Alloy Steel Tubes (American Society of Testing Materials, 2009)
This specification covers minimum-wall-thickness, seamless and electric-resistance welded, low-alloy steel tubes for pressure containing parts such as economizers or other applications where corrosion resistance is important.